School location factors and learners access to the universal basic education programme facilities in Edo State, Nigeria (2019)
The problem of access, equity and quality are of concern to stakeholders due to perceived decline in numeracy and literacy in Nigeria. Insinuations are that the UBE programme is failing. Previous researches pinpointed funding among others. Some other factors yet to be well investigated include locational factors; home distance, rural - urban settings and school site as they influence access (enrolment) to UBE in Edo state (2010 - 2015). The survey research design with a population consisting of all public primary schools was adopted. The Multi-stage sampling procedure was adopted to select 1 senatorial district (Edo North). Various sampling techniques were used to select 998 primary 6 pupils and 786 Junior secondary school students. Two instruments titled ‘School Location Factors and School Access Questionnaire 1 & 2’ (SLFSAQ) guided the study. SLFSAQ 1 is a checklist while SLFSAQ 2 (r-0.85) elicited primary information. SLFSAQ 2 is designed after the Likert scale type. Instrument validity was established by colleagues in the Department of Educational Management, University of Ibadan. 5 research questions and 5 hypotheses guided the study. The hypotheses were analysed using chi- square for hypotheses 1, 2 and 3 while multiple regression analysis was adopted for hypotheses 4 and 5 @ p<0.05. A significant relationship existed between home distance and school location X2(df =15.27) =2087.16; p<0.05. Also, a significant relationship exist between rural-urban location and access to schools Ai(df=2,27) =1088.73; p<0.05. The relationship between school site and learners acess is X2 (df=27,30)=2071.13. The independent variables jointly contributed to access to UBE R=0.687 while F =df (3.16287) = 26.605, p<0.05. Geographical location made the highest contribution P=0.186; p<0.05. Recommendations included the need for more mass mobilisations especially in rural areas, schools should be located in centrally accessible areas with modest distribution of resources (personnel).